GIS-based risk assessment of tropical surface water pollution by integrating hydrogeological and anthropogenic parameters - Saifuddin, Muhammad Firdaus Umar; Ash’aari, Zulfa Hanan; Aris, Ahmad Zaharin; Diyana, Zed (Taylor & Francis, 2022)
Surface water pollution is a huge issue worldwide that keeps growing in magnitude and complexity which leads to millions of people don’t have access to clean water resource. Numerous studies on vulnerability, hazard and risk assessment of water pollution had been conducted yet most of them only focused on one of the three risk components. Therefore, the objective of this study was to apply a geospatial approach that integrated hydrogeological and anthropogenic parameters to assess the risk of surface water pollution in Selangor River Basin, Malaysia. Analytical Hierarchy Process (AHP) and Weighted Linear Combination (WLC) were applied in hydrogeological vulnerability assessment. WRASTIC index was used in anthropogenic hazard assessment. The risk map showed that high-risk zones were mainly located in areas where development and agricultural activities are extensive. Conversely, low-risk zones were in areas that were mostly covered by forest with few developments, such as the upstream region. The results also revealed that high and very risk levels were dependent on soil media and presence of land use and anthropogenic activity especially agriculture, industry, and wastewater presence. The risk map also showed that developed area with high hydrogeological vulnerability would have higher risk of pollution compared to areas without any anthropogenic hazard. The risk map can assist stakeholders to identify at risk of pollution. This allows for better decision-making in integrated river basin management.